Spatial knowledge for risks prevention and mitigation: The civil protection planning of the Abruzzo Region - Di Ludovico, Donato; Di Lodovico, Luana; Basi, Maria (TeMA - Journal of Land Use, Mobility and Environment, 2021)
The scientific research described in this paper concerns the theme of Civil Protection Planning at Regional level and Disaster Risk Management. In particular, it concerns the definition and experimentation of a particular model of basic Knowledge System. This model, which has been tested within the definition and predisposition of the ‘Knowledge elements of the Abruzzo Region territory and civil protection organization of the Abruzzo Region (It)’, is the result of a continuous and dynamic technical-scientific action, whose structure must necessarily be flexible in order to collect and analyse data and information concerning themes, the risks, which are constantly changing. In the research, an original analytical methodology of the Knowledge System has become the basis for the experimentation of a Regional Management Risk Plan (case study Abruzzo Region), a part of the Regional Civil Protection Plan, which allows to identify the Hotspots, i.e. areas characterized by very high and probably simultaneous risks, in which it is strictly necessary to identify prevention and mitigation interventions, the ‘Territorial Prevention and Recovery Projects’ that concern the structural activities of civil protection. The next steps will concern the definition of the methodology for the construction of a Digital Knowledge Platform for the establishment of a Spatial Information Modeling.